MEASURING THE LEVEL OF FRAUD ON FINANCIAL STATEMENTS: MODEL OF FRAUD TRIANGLE (Case Studies on Companies Listed on the Indonesia Stock Exchange in 2014-2018) (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2021)
This study aims to measure the level of fraudulent financial statements with the fraud triangle model. The independent variables are pressure, opportunity, rationalization, and the dependent variable is fraudulent financial statements. The population in this study is companies listed on the Indonesia Stock Exchange (IDX) in 2014-2018 with a sample of 100 companies. Data analysis techniques using multiple linear regression. The results show that the pressure with proxies the financial stability and financial target and the opportunity with proxy the nature of industry has significant effect on the financial statement fraud. Meanwhile, the opportunity with proxies the ineffective monitoring and rationalization have not significant effect on the financial statement fraudulent.